2022
DOI: 10.1159/000522066
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Earplugs and Eye Masks Usage in the Intensive Care Unit on Sleep Quality: Systematic Review

Abstract: <b><i>Introduction:</i></b> Patients in the intensive care unit (ICU) have severe and complex disease characteristics and their sleep problems should not be ignored. Poor-quality sleep is associated with impaired immune function and associated susceptibility to disease and infection, decreased energy levels, delirium, delays in recovery. This study is conducted to examine the results of studies examining sleep quality using earplugs and eye masks in the ICU. <b><i>Methods:&l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…Systematic review study by Polat et al earplugs and eye masks were found to have potential positive effects on sleep quality and delirium incidence. Also using earplugs and eye masks is a noninvasive, economical, and effective way to improve sleep quality in ICU patients 35 . Secondary objectives of this study were to measure the parameters thought to have an effect on delirium. Sleep quality : One important problem for ICU patients is the disruption of the sleep–wake cycle and its negative effects on patients' cognitive status 12,36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic review study by Polat et al earplugs and eye masks were found to have potential positive effects on sleep quality and delirium incidence. Also using earplugs and eye masks is a noninvasive, economical, and effective way to improve sleep quality in ICU patients 35 . Secondary objectives of this study were to measure the parameters thought to have an effect on delirium. Sleep quality : One important problem for ICU patients is the disruption of the sleep–wake cycle and its negative effects on patients' cognitive status 12,36 .…”
Section: Discussionmentioning
confidence: 99%
“…Also using earplugs and eye masks is a noninvasive, economical, and effective way to improve sleep quality in ICU patients. 35 Secondary objectives of this study were to measure the parameters thought to have an effect on delirium.…”
Section: B Level Of Sedation and Level Of Consciousnessmentioning
confidence: 99%
“…Hu et al (2015) investigated the effect of using earplugs and eye masks on sleep quality and melatonin levels in ICU patients and concluded that the use of earplugs and eye masks improved sleep and increased melatonin levels. In systematic reviews evaluating the short-and long-term benefits of eye masks and earplugs, they were found to have a positive effect on sleep quality (Fang et al, 2021;Locihová et al, 2018;Polat et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al (2015) investigated the effect of using earplugs and eye masks on sleep quality and melatonin levels in ICU patients and concluded that the use of earplugs and eye masks improved sleep and increased melatonin levels. In systematic reviews evaluating the short‐ and long‐term benefits of eye masks and earplugs, they were found to have a positive effect on sleep quality (Fang et al, 2021; Locihová et al, 2018; Polat et al, 2022). In a different meta‐analysis, it was reported that eye masks and earplugs provided a significant increase in total sleep time, sleep efficiency, REM time, and a significant decrease in awakening (Karimi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation